Combined Utilization of Cylinder and Different Shaped Alumina Nanoparticles in the Base Fluid for the Effective Cooling System Design of Lithium-Ion Battery Packs - Selimefendigil, Fatih; Dilbaz, Furkan; Öztop, Hakan Fehmi (Mdpi, 2023)
It is important to consider the thermal management of lithium-ion batteries to overcome their limitations in usage and improve their performance and life cycles. In this study, a novel cooling system for the thermal management of lithium-ion battery packs is proposed by using an inner cylinder in the cooling channel and different-shaped nanoparticles in the base fluid, which is used as the cooling medium. The performance improvements in a 20 Ah capacity battery are compared by using a water-boehmite alumina (AlOOH) nanofluid, considering cylinder-, brick-, and blade-shaped nanoparticles up to a solid volume fraction of 2%. The numerical analysis is conducted using the finite element method, and Reynolds numbers between 100 and 600 are considered. When the efficacy of the coolants utilized is compared, it is apparent that as the Reynolds number increases, both cooling media decrease the highest temperature and homogenize the temperatures in the battery. The utilization of the cylinder in the mini-channel results in a 2 degrees C temperature drop at Re = 600 as compared to the flat channel. A boehmite alumina nanofluid with a 2% volume fraction reduces the maximum temperature by 5.1% at Re = 200. When the shape effect of the nanofluid is examined, it is noted that the cylinder-shaped particle improves the temperature by 4.93% as compared to blade-shaped nanoparticles and 7.32% as compared to brick-shaped nanoparticles. Thus, the combined utilization of a nanofluid containing cylindrical-shaped nanoparticles as the cooling medium and a cylinder in the mini-channel of a battery thermal management system provides an effective cooling system for the thermal management of the battery pack. The outcomes of this work are helpful for further system design and optimization studies related to battery thermal management.
Keywords: nanoparticle shape; cylinder; thermal management; lithium-ion battery pack; finite element method